Fresh Gastrodia elata Blume alleviates simulated weightlessness-induced cognitive impairment by regulating inflammatory and apoptosis-related pathways - Zhang, Yiwen; Huang, Hong; Yao, Caihong; Sun, Xinran; He, Qinghu; Choudharyc, Muhammad Iqbal; Chen, Shanguang; Liu, Xinmin; Jiang, Ning (Frontiers in Pharmacology, 2023)
In aerospace medicine, the influence of microgravity on cognition has always been a risk factor threatening astronauts’ health. The traditional medicinal plant and food material Gastrodia elata Blume has been used as a therapeutic drug for neurological diseases for a long time due to its unique neuroprotective effect. To study the effect of fresh Gastrodia elata Blume (FG) on cognitive impairment caused by microgravity, hindlimb unloading (HU) was used to stimulate weightlessness in mice. The fresh Gastrodia elata Blume (0.5 g/kg or 1.0 g/kg) was intragastrically administered daily to mice exposed to HU and behavioral tests were conducted after four weeks to detect the cognitive status of animals. The behavioral tests results showed that fresh Gastrodia elata Blume therapy significantly improved the performance of mice in the object location recognition test, Step-Down test, and Morris Water Maze test, including short-term and long-term spatial memory. According to the biochemical test results, fresh Gastrodia elata Blume administration not only reduced serum factor levels of oxidative stress but also maintained the balance of pro-inflammatory and anti-inflammatory factors in the hippocampus, reversing the abnormal increase of NLRP3 and NF-κB. The apoptosis-related proteins were downregulated which may be related to the activation of the PI3K/AKT/mTOR pathway by fresh Gastrodia elata Blume therapy, and the abnormal changes of synapse-related protein and glutamate neurotransmitter were corrected. These results identify the improvement effect of fresh Gastrodia elata Blume as a new application form of Gastrodia elata Blume on cognitive impairment caused by simulated weightlessness and advance our understanding of the mechanism of fresh Gastrodia elata Blume on the neuroprotective effect.